Magnetic resonance imaging in the evaluation of cesarean scar defect - Wu Shun Felix Wong; Wing Tak Fung (Wolters Kluwer Medknow Publications, 2018)
The incidence of Cesarean scar defect (CSD) would increase with the increasing trends of cesarean section delivery. The actual incidence of this condition is unknown, but it had been estimated by hysteroscopy, sonohysterography, or transvaginal ultrasound to be around 50% of patients with cesarean section. CSD is often asymptomatic, but it may produce common symptoms such as abnormal uterine bleeding, infertility, and pelvic pain. Adverse pregnancy outcomes with scar ectopic pregnancy, uterine rupture had been reported. The use of magnetic resonance imaging (MRI) imaging of this condition is seldom performed and reported. This paper is to analyze retrospectively the MRI finding of 158 women, so as to review the MRI findings of CSD, their appearances and measurements.